Using the reduced La(Co,Cu)03 nanoperovskites as catalyst precursors for CO hydrogenation - Thao, Nguyen Tien; Thuan, Ngo Thi; Kaliaguine, Serge (VNU Journal of Science: Natural Sciences and Technology, 2009)
Abstract